Conditional cash transfers, political participation, and voting behavior - Javier Eduardo Báez Ramírez; Adriana Camacho; Emily Conover; Román Andrés Zárate (Institute for the Study of Labor (IZA), 2012)
This paper estimates the effect of enrollment in a large scale anti-poverty program in Colombia, Familias en Acción (FA), on intent to vote, turnout and electoral choice. For identification we use discontinuities in program eligibility and variation in program enrollment across voting booths. We find that FA has a positive effect on political participation in the 2010 presidential elections by increasing the probability that program beneficiaries register to vote and cast a ballot, particularly among women. Regarding voter's choice, we find that program participants expressed a stronger preference for the official party that implemented and expanded the program. Overall, the findings show that voters respond to targeted transfers and that these transfers can foster support for incumbents, thus making the case for designing political and legislative mechanisms, as the laws recently passed by the Colombian government, that avoid successful anti-poverty schemes from being captured by political patronage.
Keywords: O10; D72; P16; 330; Conditional Cash Transfers; voting behavior; Colombia; Armutspolitik; Partizipation; Wahlverhalten; Kolumbien